Active polylactic acid/tilapia fish gelatin-sodium alginate bilayer films: Application in preservation of Japanese sea bass (Lateolabrax japonicus). (September 2022) - Chen, Jingwen; Li, Yinxuan; Wang, Yifen; Yakubu, Salimata; Tang, Haibing; Li, Li
Abstract: Most edible films/coatings including those made of gelatin cannot be used independently as packaging films. In this study, active fish gelatin-based bilayer packaging films were developed and applied to preserve Japanese sea bass. The coating method was applied to produce polylactic acid/tilapia fish gelatin-sodium alginate bilayer film (PLA/FGSA). β -cyclodextrin inclusion complexes of cinnamaldehyde ( β -CD-CI) and thymol ( β -CD-Ty) were added into the gelatin-based layer of the PLA/FGSA to obtain active bilayer films (PLA/FGSA-CI and PLA/FGSA-Ty). This combination improved the oxygen and water vapor barrier abilities of the films, compared with PLA and edible gelatin-based monolayer films. Both active bilayer films possessed strong antibacterial and antioxidant activities. PLA/FGSA-Ty film showed the most effective inhibition against the growth of Pseudomonas .spp and H2 S-producing Shewanella, generation of total volatile basic nitrogen (TVB-N) and thiobarbituric acid reactive substances (TBARS) of fish meat. These results indicate the active bilayer films are promising in the preservation of seafood. Graphical Abstract: ga1 Highlights: PLA/FGSA based active bilayer films were developed and applied to sea bass. Bilayer films own better barrier abilities than PLA and gelatin-based monolayer films. Addition of β -CD-CI/ β -CD-Ty into PLA/FGSA film enhanced its active activities. Active PLA/FGSA films inhibited the growth of SSOs in sea bass. The gelatin-based bilayer films can be used dependently as food packaging films.